Experimental and numerical modeling of high speed ice impact onto rigid target - Heng, Fangming (Cranfield University, 2015)
The core goal of this research is to develop an ice impact modelling methodology for ice impact on aircraft structures. The main current limitation of ice impact analysis is the ice constitutive model, so this research is focussed on the assessment and improvement of current ice constitutive models. Centre on this aim three aspect works has been done. First, investigating the ice mechanical properties. Through literature review 8 properties of ice have been identified as crucial properties of ice when modelling ice or assessing the ice material model. Secondly, assessing the current material models theoretically and numerically and identify areas where improvements can be made to current ice constitutive models. Five existing ice material models are investigated through theoretical study. Two of them, MAT 13 and MAT 155, are available to use in the LS-Dyna and have been tested through modelling 3 different test problems. Through the investigation of the ice model, MAT 155 is proved to be the optimum ice material model as it reflects the most features (including the compaction feature, bilinear hardening, pressure based failure mode, strain rate dependence) of ice. Through the research of MAT 155, three modified methods of MAT 155 are proposed. Thirdly, developing an implementation of an ice constitutive model as a tool for future assessment of improvements to ice modelling. An LS-Dyna user defined material model (UMAT) based on MAT 155 has been built up and modified by adding the pressure dependence feature. Through the building up and verification of UMAT, two features of MAT 155 were found to perform differently than was described in Carney’s article. The Drucker Prager-yield function was chosen to reflect the pressure dependence of the ice and the routine describing the Drucker-Prager yield function has been proved that it can work properly in the simulation. Based on the investigated ice material model, the pressure dependent feature is added into this user defined material model.
Keywords: LS-Dyna; UMAT; pressure dependent yield criteria; MAT 155; ice model assessment